Are fission–fusion dynamics consistent among populations? A large‐scale study with Cape buffalo. Issue 17 (11th August 2020) - Wielgus, Elodie; Cornélis, Daniel; de Garine‐Wichatitsky, Michel; Cain, Bradley; Fritz, Hervé; Miguel, Eve; Valls‐Fox, Hugo; Caron, Alexandre; Chamaillé‐Jammes, Simon
Abstract: Fission–fusion dynamics allow animals to manage costs and benefits of group living by adjusting group size. The degree of intraspecific variation in fission–fusion dynamics across the geographical range is poorly known. During 2008–2016, 38 adult female Cape buffalo were equipped with GPS collars in three populations located in different protected areas (Gonarezhou National Park and Hwange National Park, Zimbabwe; Kruger National Park, South Africa) to investigate the patterns and environmental drivers of fission–fusion dynamics among populations. We estimated home range overlap and fission and fusion events between Cape buffalo dyads. We investigated the temporal dynamics of both events at daily and seasonal scales and examined the influence of habitat and distance to water on event location. Fission–fusion dynamics were generally consistent across populations: Fission and fusion periods lasted on average between less than one day and three days. However, we found seasonal differences in the underlying patterns of fission and fusion, which point out the likely influence of resource availability and distribution in time on group dynamics: During the wet season, Cape buffalo split and associated more frequently and were in the same or in a different subgroup for shorter periods. Cape buffalo subgroups were more likely to merge than to split in open areas located near water, but overall vegetation and distance to water were very poor predictors of where fission and fusion events occurred. This study is one of the first to quantify fission–fusion dynamics in a single species across several populations with a common methodology, thus robustly questioning the behavioral flexibility of fission–fusion dynamics among environments. Abstract : The frequency at which Cape buffalos split and join allows them to adjust to environmental conditions. In 3 distinct populations, the associations between individuals last on average between 1 and 3 days, but seasonal differences exist: In the dry season, buffalos split and join less frequently but stay in the same subgroup for longer periods than in wet season. Vegetation openness and distance to water are poor predictors of where fission and fusion events occur.